Nutrient Requirements and Basics of Nutritional Status Assessment Malnutrition Problems - Sehfiani, Indah (Seulanga : Jurnal Pendidikan Anak, 2024)
This article examines the critical importance of nutrition for children from birth to six years of age, a period identified as the "golden age" for development. The author argues that adequate nutritional intake during these formative years is a key determinant in the holistic development of a child's character, personality, and cognitive abilities. The paper highlights the responsibility of both parents and educators in monitoring and ensuring that children's dietary needs are met to foster optimal growth and prevent illness. It discusses the common issue of children consuming snack foods with low nutritional value, which can lead to various health problems. Furthermore, the article outlines the essential nutrients required at different stages of early childhood and details methods for assessing nutritional status, including anthropometric and clinical evaluations. The text also addresses prevalent malnutrition problems in Indonesia, such as Protein-Energy Malnutrition, Vitamin A deficiency, Iodine Deficiency Disorder, Iron-Deficiency Anemia, and overnutrition. The author concludes by emphasizing that a comprehensive understanding of nutritional requirements and potential deficiencies is essential for caregivers to support healthy development in early childhood.